Mengenal Istilah Bulan Dalam Kalender Jawa Pada Kehidupan Masyarakat Jawa: Kajian Etnolinguistik: (Getting to Know the Terms of Month in the Javanese Calendar in Javanese Community Life: Ethnolinguistic Study) - Iliya Ulva; Uut Istianah (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This research aims to describe the use of lunar terms in the Javanese calendar in people's lives and reveal the meaning and cultural values ​​contained therein. The research method used is subjective exploration with triangulation data collection techniques, inductive data examination, and subjective questioning. The research results show that Javanese people use lunar terms in the Javanese calendar in various aspects of life, such as determining dates, mentioning events, carrying out traditions, calculating good days, mentioning age, and strengthening cultural identity. The use of the term Javanese month contains quite deep meaning and cultural values, including cultural adaptation, local wisdom, religiosity, oral traditions and cultural identity. The term month in the Javanese calendar is not just a translation. This is a reflection of how Javanese culture adapts, respects local wisdom, and upholds religious values ​​and oral traditions. The use of this term in everyday life is an affirmation of Javanese cultural identity which continues to be preserved.